Laboratory diagnosis of human brucellosis in Egypt and persistence of the pathogen following treatment - Marei, Ayman; Boghdadi, Ghada; Abdel-Hamed, Nahla; Hessin, Rasha; Abdoel, Theresia; Smits, Henk; Fathey, Fayza (The Journal of Infection in Developing Countries, 2011)
Introduction: Brucellosis is a major public health problem in Egypt. The Brucella IgM/IgG lateral flow assay was developed as a point-of-care test for the diagnosis of human brucellosis. The aim of this study was to assess the diagnostic value of the lateral flow assay for use in Egypt. Methodology: Fifty samples of patients who presented with clinical suspicion of brucellosis over a one-year period were collected. All samples were subjected to the Brucella IgM/IgG lateral flow assay, serum agglutination test (SAT), rose bengal RB Test (RB), 2- mercapteoethanol (2-ME), culture and PCR. SAT, 2- ME, culture and PCR were retested after the end of the treatment. Results: Culture and SAT confirmed the diagnosis of brucellosis in twenty patients. While 90% of the samples were positive by SAT, only 30% and 85% were positive by culture and PCR respectively. The sensitivity of the lateral flow assay calculated for the Brucella IgM/IgG was 95% and specificity was 97%. Conclusion: These data show that the lateral flow assay is more suitable for diagnosis of brucellosis in Egypt than culture and SAT. Application of the PCR on serum samples collected during follow-up revealed that the DNA of the pathogen was yet not completely cleared almost 60 days after the start of treatment with doxycycline and ciprofloxacin.